Incidence, Risk Factors and Outcome of Gallbladder Perforation during Laparoscopic Cholecystectomy - Zahoor Ahmed, Naveed Ullah Khan, Javed Ahmad, Sarwat Saeed, Syeda Fatima Batool, Asad Sami, Maria Zafar, Ailiya Khawar (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Gallbladder perforation has been recorded in patients undergoing laparoscopic cholecystectomy and associated with the development of gallstones and bile leakage. The present study investigated the incidence, risk factors, and outcome of gallbladder perforation in patients undergoing elective laparoscopic cholecystectomy. Patients and Methods: This prospective study was conducted on 156 patients who underwent laparoscopic cholecystectomy in the department of General Surgery, Federal Government Polyclinic Hospital, Islamabad from January 2021 to July 2022. Gallbladder stone patients with chronic symptoms such as vomiting, recurrent episodes of epigastric, nausea, and hypochondrial pain on right side were included. Acute cholecystitis patients with single or multiple gallstone disease were also enrolled. All the patients were prepared for laparoscopic cholecystectomy and investigations such as blood sugar, liver function test, CBC, blood urea and creatinine, ultrasound of gallbladder, and ECG were done. SPSS version 26 was used for data analysis. Results: Of the total 156 patients, there were 126 (80.8%) females and 30 (19.2%) male. Age-wise distribution of patients were as follows: 66 (42.3%) in 20-35 years, 52 (33.3%) in 36-50 years, and 38 (24.4%) in 51-65 years. The incidence of single gall stone (SGS), multi gallstones (MGS), and acute cholecystitis was 48 (30.8%), 88 (56.4%), and 20 (12.8%) respectively. The overall mean age was 36 years. The incidence of gallbladder perforation was 26.9% (n=42) among all patients. Patients distribution based on gallbladder perforation were as follows: 17 (10.9%) in MGS, 14 (9.0%) in SGS, and 11 (7.1%) in acute cholecystitis cases. Conclusion: The present study found that the prevalence of gallbladder perforation was 26.9% among SGS, MGS, and acute cholecystitis. Majority of GB perforation occurred during gallbladder bed dissection. Acute cholecystitis patients are more prone to GB perforation. GB perforation can be reduced by utilization of harmonic scalpel in laparoscopic cholecystitis. Keywords: Elective laparoscopic cholecystectomy, Gallbladder perforation, Outcomes